Potensi dan Strategi Pengembangan Duku Bacan (lansium domesticum corr.) Di Desa Amasing Kali Kabupaten Halmahera Selatan - suryanti suryanti; Zauzah Abdullatif; Sri Soenarsih DAS (Jurnal Pertanian Khairun, 2022)
ABSTRACTThe main objectives of the present study were to identify the potency to develop the Duku Bacan commodity and to formulate the development strategy of the Duku Bacan Cultivation in the Amasing village of South Halmahera Regency. The samples were collected from 51 Duku growersusing theÂ Purposive Random Sampling method. The data were then analyzed descriptively and quantitatively. The quantitative statistical analyses include the analysis of potency (the density index of Duku Bacan trees, the plant productivity of Duku Bacan, and the potency analysis of Duku Bacan plant), Location Quotient (LQ) analysis, and trading margin analysis. Meanwhile, the qualitative analyses consist of the analyses of land suitability, institutional system, and marketing system of Duku. The SWOT analysis was applied to formulate the development strategy, whilst the priority of the development strategy for Duku Bacan was analyzed using the Analytical Hierarchy Process (AHP) model. The findings revealed that the age of Duku growers was classified into the productive age group with the average educational background level was elementary-school. The traditional farming system was predominantly applied by the growers with low or the absence of a technology input. The potency of Duku Bacan plants in Amasing Kali Village of South Halmahera Regency was identified from the yield that reached up to 2,381 tonnes/hectare with the potency of 176,2 Kg per year. The LQ 1 means that Duku Bacan plant is considered the priority local commodity. The lands in Amasing Kali village are suitable for growing Duku and there are 2 (two) marketing channels for Duku developed in this village. The development strategy of Duku Bacan cultivation in Amasing Kali village based on the scale of priority include the enhancement of the roles of Local Government, the establishment of farmer group institution, the increase of farmer capacity, the optimization of duties and roles of extension workers, the increase of plant production, the optimization of potential land use, strengthening the agribusiness system of Duku and promotion,Â  and also the utilization of economic agencies.Keywords: Duku Bacan, potency, strategy, development